Realizing World-Class Port with International Direct Call At Kariangau Port, Balikpapan - Ratna Kurnia Dewi; Haryani, Haryani (Cita konsultindo, 2023)
International Direct Call is a method of shipping containers directly from domestic ports to foreign ports of destination without making any stops at domestic ports. The East Kalimantan region now has an international connection thanks to the International Direct Call from Kariangau Port, managed by PT Pelindo IV and PT Kaltim Kariangau Terminal (KKT). The introduction of direct calls through the Port of Balikpapan has boosted the economy of East Kalimantan and its environs on a broader scale. One is lessening planned operations expenses for USD 300-500 for each compartment and decreasing the span of ware shipments to various commodity objective nations. This research focuses on the development and management of international direct calls, as well as the threats and roles of related institutions at the Kariangau port in Balikpapan. Using qualitative descriptive analysis, the researchers collected data through in-depth interviews and direct field observations. It is known from this research that: It has been demonstrated that Pelindo IV's International Direct Call program improves the time and cost efficiency of export activities. For instance, exports to China now take just 16 days instead of the previous 24 days, exports to Japan now take 18 days instead of the previous 28 days, and exports to Korea now take 17 days instead of the previous 26 days. Additionally, the expense per holder has been diminished radically, from arriving at IDR 4 million for each compartment to just around IDR 792 thousand for every compartment. According to Pelindo IV's calculations, the export time to Shanghai, China, will be reduced from 25 to 30 days for direct calls from Balikpapan to 9 days. The port of Kariangau, Balikpapan, has become a world-class pioneer in the New Capital Region thanks to this remarkable achievement.